An experimental study on compressive behaviour of cemented rockfill. (20th July 2019) - Jiang, Haiqiang; Fall, Mamadou; Li, Yuanhui; Han, Jing
Highlights: Technical information and data for better optimization and design of cemented rockfill (CRF) are presented. Strength and stress-strain behaviour of CRF are a function of the packing density of the aggregates. CRF with coarser particles and the best grain size distribution has the highest strength. Addition of sand can increase the strength of CRF. A partial replacement of ordinary Portland cement with fly ash improves the strength of the CRF. Abstract: Cemented rockfill (CRF) has more superior mechanical properties (e.g., compressive strength, stiffness, cohesion and friction angle) over other types of backfill material, such as cemented paste backfill (CPB) and hydraulic fill, with the same amount of binder. A comprehensive understanding of the mechanical performance of CRF is critical for effectively applying CRF technology to underground mines. In this paper, the effects of aggregate gradation, the addition of sand, and binder content and type on the uniaxial compressive strength (UCS) and stress-strain behaviour of CRF are experimentally investigated for up to 90 days of curing. The results show that CRF with coarser particles and the best grain size distribution has the highest strength over that with uniform-sized rock aggregate, and the strength of the CRF increases with increased maximum particle size of the rock aggregate. The strength of the CRF increases in proportion with the amount of ordinary Portland cement (OPC). The addition of sand enhances the strength of the CRF samples; the extent of the increase in strength depends on the sand/aggregate replacement ratio. A partial replacement (20–50%) of OPC with fly ash (FA) appears to improve the strength of the CRF samples due to the micro-filler effect, whereas a negative effect is observed when blast furnace slag (Slag) with relatively low strength activity index is used instead. Moreover, the stress-strain response of CRF is strongly influenced by the curing age, aggregate gradation, addition of sand, and binder content and type. The results of this investigation provide technical information for designing cost-effective, safe and durable CRF structures in underground mines.